The Impact of trade liberalization policy on Tanzanian agriculture sector - VYAGUSA, Pascal Dismas (KDI School, 2017)
This thesis examines the effects of trade liberalization policies on Tanzanian agriculture sector. The study used the annual time series data covering the period of 24 years from 1990 to 2014. The data were regressed by using Feasible Generalized Least Square Method (FGLS) to test the relationship between agricultural production growth and trade variables which were affected by liberalization policies. Those trade variables are Tariff rate of primary products, FDI to Agriculture, Credits to Agriculture and Percentage of annual change in agriculture. The empirical findings of this study showed that, some trade liberalization measures adopted in the mid - 1980s have resulted to the positive impact on the production growth of the Tanzanian agriculture sector. The changes which were made to the tariff rates as the adoption of trade liberalization policies resulted to positive growth on agricultural production. Statistics shows that, the tariff rate has been constantly decreasing since the adoption of trade liberalization policies which resulted to increase in agricultural production. However, some trade indicators, the foreign direct investment and credits which go to agriculture were not statistically significant. This may be explained that the efforts which have been put to attract the foreign direct investment in the agriculture sector and the credit which have been channeled to the agriculture sector have no impacted significantly On the other hand percentage of annual changes in agricultural area was a negatively related to the agricultural production growth. The statistics supports that there is high change in the agricultural land to other non agricultural sectors such as mines, housing and service which cause the decrease in the agricultural production.
Thesis(Master) --KDI School:Master of Development Policy,2017